Genital malformations in newborns of female nickel-refinery workers - Vaktskjold, Arild; Talykova, Ljudmila Vasiljevna; Chashchin, Valerij Petrovitsj; Nieboer, Evert; Thomassen, Yngvar; Odland, Jon Øyvind (Scandinavian Journal of Work, Environment & Health, 2006)
' ' OBJECTIVES ': 'This study investigated whether pregnant women employed in nickel-exposed work areas are at elevated risk of delivering a newborn with a genital malformation. ' ' METHODS ': 'In this register-based cohort study, data about pregnancy outcome and occupation were obtained using the Kola Birth Registry. Each record in the Registry was assigned a categorical nickel exposure rating according to the occupation the delivering woman had at the time of becoming pregnant, using, as guidelines, the water-soluble nickel subfraction of the inhalable aerosol fraction obtained by personal monitoring for nickel-refinery workers or the measured urinary nickel concentrations. The reference population comprised delivering women from Moncegorsk with a background exposure level. The association of the outcome with the assigned exposure ratings was analyzed in a logistic regression model, adjusted for parity, maternal malformation, exposure to solvents, and infection in early pregnancy. ' ' RESULTS ': 'The odds ratio for nickel-exposed women delivering a newborn with a genital malformation was 0.81 [95% confidence interval (95% CI) 0.52–1.26], and that for an undescended testicle was 0.76 (95% CI 0.40–1.47). ' ' CONCLUSIONS ': 'In this study no negative effect of maternal exposure to water-soluble nickel was found on the risk of delivering a newborn with malformations of the genital organs. The results should be interpreted with caution since there were few cases in the higher exposure groups. The findings do not exclude the possibility of an effect on the risk of other congenital malformations and adverse outcomes (including reduced fertility).
Keywords: cryptorchidism; female; genital malformation; hypospadias; newborn; nickel; nickel-refinery worker; occupational exposure; registry; Russia